Convert -11 Fahrenheit to Celsius

What is -11 degrees Fahrenheit in Celsius? Just type in either box, and the number in the other box will be converted automatically.
Fahrenheit
Celsius
-11° Fahrenheit = -23.89° Celsius
(rounded to 4 digits)
How hot is -11 degrees Fahrenheit? How cold? Convert between Fahrenheit and Celsius.
More temperatures starting with -11 degrees in Fahrenheit
Note: results are rounded
-11.00 °F = -23.89 °C -10.75 °F = -23.75 °C -10.50 °F = -23.61 °C -10.25 °F = -23.47 °C
-10.99 °F = -23.88 °C -10.74 °F = -23.74 °C -10.49 °F = -23.61 °C -10.24 °F = -23.47 °C
-10.98 °F = -23.88 °C -10.73 °F = -23.74 °C -10.48 °F = -23.60 °C -10.23 °F = -23.46 °C
-10.97 °F = -23.87 °C -10.72 °F = -23.73 °C -10.47 °F = -23.59 °C -10.22 °F = -23.46 °C
-10.96 °F = -23.87 °C -10.71 °F = -23.73 °C -10.46 °F = -23.59 °C -10.21 °F = -23.45 °C
-10.95 °F = -23.86 °C -10.70 °F = -23.72 °C -10.45 °F = -23.58 °C -10.20 °F = -23.44 °C
-10.94 °F = -23.86 °C -10.69 °F = -23.72 °C -10.44 °F = -23.58 °C -10.19 °F = -23.44 °C
-10.93 °F = -23.85 °C -10.68 °F = -23.71 °C -10.43 °F = -23.57 °C -10.18 °F = -23.43 °C
-10.92 °F = -23.84 °C -10.67 °F = -23.71 °C -10.42 °F = -23.57 °C -10.17 °F = -23.43 °C
-10.91 °F = -23.84 °C -10.66 °F = -23.70 °C -10.41 °F = -23.56 °C -10.16 °F = -23.42 °C
-10.90 °F = -23.83 °C -10.65 °F = -23.69 °C -10.40 °F = -23.56 °C -10.15 °F = -23.42 °C
-10.89 °F = -23.83 °C -10.64 °F = -23.69 °C -10.39 °F = -23.55 °C -10.14 °F = -23.41 °C
-10.88 °F = -23.82 °C -10.63 °F = -23.68 °C -10.38 °F = -23.54 °C -10.13 °F = -23.41 °C
-10.87 °F = -23.82 °C -10.62 °F = -23.68 °C -10.37 °F = -23.54 °C -10.12 °F = -23.40 °C
-10.86 °F = -23.81 °C -10.61 °F = -23.67 °C -10.36 °F = -23.53 °C -10.11 °F = -23.39 °C
-10.85 °F = -23.81 °C -10.60 °F = -23.67 °C -10.35 °F = -23.53 °C -10.10 °F = -23.39 °C
-10.84 °F = -23.80 °C -10.59 °F = -23.66 °C -10.34 °F = -23.52 °C -10.09 °F = -23.38 °C
-10.83 °F = -23.79 °C -10.58 °F = -23.66 °C -10.33 °F = -23.52 °C -10.08 °F = -23.38 °C
-10.82 °F = -23.79 °C -10.57 °F = -23.65 °C -10.32 °F = -23.51 °C -10.07 °F = -23.37 °C
-10.81 °F = -23.78 °C -10.56 °F = -23.64 °C -10.31 °F = -23.51 °C -10.06 °F = -23.37 °C
-10.80 °F = -23.78 °C -10.55 °F = -23.64 °C -10.30 °F = -23.50 °C -10.05 °F = -23.36 °C
-10.79 °F = -23.77 °C -10.54 °F = -23.63 °C -10.29 °F = -23.49 °C -10.04 °F = -23.36 °C
-10.78 °F = -23.77 °C -10.53 °F = -23.63 °C -10.28 °F = -23.49 °C -10.03 °F = -23.35 °C
-10.77 °F = -23.76 °C -10.52 °F = -23.62 °C -10.27 °F = -23.48 °C -10.02 °F = -23.34 °C
-10.76 °F = -23.76 °C -10.51 °F = -23.62 °C -10.26 °F = -23.48 °C -10.01 °F = -23.34 °C